Translating Idiormist Expressions from Arabic into English in Essam Youssef's Quarter Gram: Challenges and Strategies - Allam, Rania (جامعة القاهرة - كلية الآداب, 2019)
التعابير الاصطلاحية في حد ذاتها عبارة عن وحدات لغوية ذات جوانب دلالية وبراغماتية وثقافية مختلفة تشكل تحديات أمام عملية الترجمة للوصول إلى أقرب مقابل للمقاطع الاصطلاحية وخاصة في النصوص الأدبية. تهدف هذه الورقة البحثية إلى تحليل استراتيجيات ترجمة المصطلحات من العربية إلى الإنجليزية في رواية عصام يوسف ربع جرام (2008) والتي ترجمتها دكتورة لبنى يوسف (2009). حيث يتم تحليل التركيبات الاصطلاحية المقسمة حسب تصنيف أبو زلال (2007) للمصطلحات العربية وفرناندو (1996) للمصطلحات الإنجليزية، باستخدام نموذج انتقائي من نيدا وتابر (1982) والشاوي والمهدي (2012) وبيكر (2018). وقد كشفت الدراسة عن أن استراتيجيات ترجمة المصطلحات الأكثر استخداما هي استراتيجية ترجمة المصطلح العربي بمصطلح مشابه في المعنى والدلالة ومختلف في الصياغة والتركيب وذلك بنسبة 38.25%، وترجمة المصطلح بشكل تفسيري بنسبة 29.95%، والترجمة الجزئية لمصطلح بنسبة 12.21%، وترجمة المصطلح العربي بمصطلح مشابه في المعنى والدلالة ومشابه في الصياغة والتركيب أيضا بنسبة 9.22% وكذلك الترجمة عن طريق نقل المصطلح كما هو إلى الإنجليزية بنسبة 6.45% فقد أثبتت الدارسة أن المترجمة حافظت على الطابع الاصطلاحي بجميع إيحاءاته ودلالاته من خلال توظيف استراتيجيات بديلة مختلفة للمصطلح الموجود بالنص العربي.
Idioms per se are linguistic units with different semantic, pragmatic and cultural facets which pose some untranslatability challenges so as to render the closest interlingual source text (ST)-target text (IT) pairs, especially in literary texts. The present paper aims at investigating the strategies of translating idioms from Arabic into English in Essam Youssef's A Quarter Gram (2008) ربع جرام translated by Loubna Youssef (2009). The analytical decoding process for the idiomatic structures is classified according to Abou-Zalal (2007) for the Arabic idioms and Fernando (1996) for the English ones, using an eclectic model of Nida and Taber (1982), Al-Shawi and Mahadi (2012) and Baker (2018). It reveals that the most employed strategies are the strategy of using an idiom of a similar meaning but dissimilar in form (38.25%), translation by paraphrase (29.95%), partial translation of the idiom (12.21%), using an idiom of similar meaning and similar form (9.22%) and borrowing tire SL idiom (6.45%). The study exhibits the translator’s keenness to retain toe idiomaticity of the ST with all its implications by employing different idiomatic rendering strategies actualizing both faithfulness and acceptability of the TT.
Keywords: الدراسات اللغوية -- الترجمة -- المعايير الإصطلاحية -- التعابير الإصطلاحية -- مستخلصات الأبحاث -- الترجمة